Optimization of enzymatic pretreatment and biogas production for palm oil mill effluent (POME) - Liew, Yuh Xiu (2019)
The rapid growth in oil palm industry has caused huge amount of waste biomass being produced. One of the highly polluting wastewater generated is known as Palm Oil Mill Effluent (POME). POME has strong wastewater characteristics due to the high content of biodegradable organic matter. Currently, the most widely adopted treatment method is anaerobic digestion. However, the current anaerobic method used requires longer retention times, low overall degradation efficiency and could hardly meet the progressively stringent Environmental Quality Act (EQA) 1974 requirements. Therefore, this research aims to improve the anaerobic digestion by implementing enzymatic pre-treatment prior to the anaerobic digestion. With a clear understanding of the effect of enzymes on hydrolysis, the enzymatic pre-treatment can be optimized and thereby improving the overall digestibility of POME. This will in turn enhance the anaerobic digestion and increase the yield of biogas.